Multiphase Flow Meters Targeting Oil & Gas Industries. (1st December 2020) - Meribout, Mahmoud; Azzi, Abdelwahid; Ghendour, Nabil; Kharoua, Nabil; Khezzar, Lyes; AlHosani, Esra
Abstract: In oil fields, multiphase flow meters (MPFMs) yield important data for proper reservoir management to maximize the oil-gas production throughput. MPFMs are also required in downstream industries such as refineries to monitor the quality of the end product and in power generation to estimate the amount of wet steam, which if its flow rate is high may damage the blade's turbines. For decades, radioactive γ-ray-based MPFM remains the most widely used and reliable device, especially for a high gas void fraction (GVF), which is however not safe and hazardous. This has prompted researchers to suggest other alternative technologies, among which some were successfully assessed either in multiphase flow loops or even in oil-gas fields. Most of these technologies still can't operate for all flow conditions and are relatively expensive hindering their wide industrial deployment. This review paper presents the most recent findings in multiphase flow metering and the main research challenges encountered in each of them. Important and significant research works are cited in an attempt to provide a reasonable cross-section of various techniques. The paper can be useful for either a fresh researcher in the area or for a skilled R&D engineer involved in the design of a MPFM.